Workshop on the Implementation of Project-Based Learning Based Independent Curriculum Teaching Tools for Vocational Teachers throughout Manggarai Regency - Marianus Tapung (Eduvest - Journal of Universal Studies, 2024)
The objective of the workshop conducted in Manggarai Regency was to enhance the competency of Vocational High School (SMK) educators in implementing Project Based Learning (PjBL)-based Curriculum Merdeka teaching tools. This initiative aimed to augment teachers' comprehension and proficiency in facilitating meaningful learning experiences within their classrooms. The workshop adopted a participatory approach wherein teachers actively engaged in designing, executing, and evaluating project-based learning activities pertinent to their specialized domains. By doing so, they were equipped with practical skills to navigate challenges such as time management, assessing learning outcomes, and effectively managing project-based classrooms. Furthermore, the workshop fostered a collaborative learning milieu that not only addressed immediate obstacles but also prepared students for the complexities of the modern workforce. The analysis of post-workshop feedback unveiled several noteworthy findings. Participants demonstrated a commendable grasp of independent curriculum concepts, proficiency in analyzing curriculum documents, and a reflective stance towards best practices. They also exhibited a strong understanding of the PjBL model, its impact, and strategies for its seamless integration into the Independent Curriculum framework.The evaluation, based on a 1-4 scale, indicated that participants rated aspects such as understanding the PjBL model, integrating it with learning challenges, and planning PjBL-based teaching projects quite positively, falling into the "already good" category with an average score of 3.6. However, areas related to testing PjBL-based teaching tools received a lower rating of 3.2, suggesting room for improvement.